Weight loss behaviour in obese patients - Skogset, Ingar (UiT Norges arktiske universitet, 2020)
Background: Obesity is increasing worldwide, and especially amongst the younger population. Many obese people are trying to lose weight without long-term success. There are certain things that they struggle with, and it can vary from patient to patient, but knowing this they can better be helped by professionals. There are many questionnaires for this purpose, most of them with many questions. Aim of study: To analyse the weight-loss behaviour in patients with obesity (BMI > 30) at baseline of treatment using the Weight Loss Behaviour Scale (WLBS). To find patterns and for behavioural differences in regards to gender, relationship status and BMI. Material and methods: Out of a total of 1150 obese patients (BMI >30) at the Centre of Obesity at Department of Gastroenterology and Nutrition at the University hospital of Northern Norway (UNN) 258 had filled out the WLBS at baseline, as part of the treatment and were included in the study. Data collection span from 2009-2017. Statistical methods: tested for normal distribution, and according to the result either parametric or non-parametric tests and correlations to compare the groups. Results: Females scored significantly higher on the total score of the WLBS questionnaire, and also in the subcategories A; "Approach to weightloss" and C; "Emotional eating". There were not any significant results concerning relationships status compared with emotional eating and physical activity that this study aimed to find out. There was a positive correlation between BMI and some of the questions; A5, B1, B3, B6, subcategory B and D, including in the total WLBS score. Conclusion: There is a difference in weight loss behaviour in gender. The obese female patients report a higher score of emotional eating and attitude towards own body weight and dieting compared to males. Being in a relationship has a positive effect on preparing and cooking food. Patients with a higher BMI seem to have more overeating and worse attitude towards physical activity. These results show that there ...